Innovative Leadership Styles In Creative Industries: A Case Study Approach (International Journal of Environmental Sciences, 2025)
Creative industries that include film and media as well as design and advertising require leadership methods which differ from standard practices. The research examines exclusive leadership methods that advance creativity along with collaborative teamwork and adaptability in creative industry sectors. A qualitative case study research design was used to gather data through five organizations representing different sectors of creativity. The research revealed that transformational leadership blended with participative styles and laissez-faire approaches turn out to be most effective in growing creative results as well as inspiring team drive. This research extends knowledge about leadership theory by demonstrating its implementation in non-standard work settings.